Performance of iterative data detection and channel estimation for single-parity check-product coded multiple antenna wireless communications - Muladi, Muladi; Fisal, N.; Yusof, S. K. (2005)
In iterative data-detection and channel-estimation algorithms, the channel estimator and the data detector recursively exchange the information order to improve the system performance. In this paper, maximum a posteriori based iterative data detection and pilot symbol assisted channel estimation of the single parity cbeck product code for multiple antenna wireless communication is studied. The finding show the algorithm can converge to a few iteration numbers and improve error probability performance of the system.